2010
DOI: 10.2174/1874431101003010065
|View full text |Cite
|
Sign up to set email alerts
|

DISTq: An Iterative Analysis of Glucose Data for Low-Cost, Real-Time and Accurate Estimation of Insulin Sensitivity

Abstract: Insulin sensitivity (SI) estimation has numerous uses in medical and clinical situations. However, highresolution tests that are useful for clinical diagnosis and monitoring are often too intensive, long and costly for regular use. Simpler tests that mitigate these issues are not accurate enough for many clinical diagnostic or monitoring scenarios. The gap between these tests presents an opportunity for new approaches.The quick dynamic insulin sensitivity test (DISTq) utilises the model-based DIST test protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…2.1 Fundamental Dynamics: Figure 1 shows the fundamental metabolic physiological dynamics considered [45,46], including primary routes of glucose appearance and delivery, insulin appearance and delivery, and their uptake and use leading to a net blood glucose level. A directly related mathematical model in [46] is validated in clinical glycemic control [47][48][49][50], insulin sensitivity testing [51][52][53][54], and virtual patients [55][56][57]. For this analysis, time-varying and steady state levels of insulin (plasma I(t) leading to interstitial Q(t) à Q SS in steady state), total nutrition (P(t) à P SS ) and glucose level (G(t) à G SS ) are used.…”
Section: Methodsmentioning
confidence: 99%
“…2.1 Fundamental Dynamics: Figure 1 shows the fundamental metabolic physiological dynamics considered [45,46], including primary routes of glucose appearance and delivery, insulin appearance and delivery, and their uptake and use leading to a net blood glucose level. A directly related mathematical model in [46] is validated in clinical glycemic control [47][48][49][50], insulin sensitivity testing [51][52][53][54], and virtual patients [55][56][57]. For this analysis, time-varying and steady state levels of insulin (plasma I(t) leading to interstitial Q(t) à Q SS in steady state), total nutrition (P(t) à P SS ) and glucose level (G(t) à G SS ) are used.…”
Section: Methodsmentioning
confidence: 99%
“…Five of the sampling protocols were based on DISTq identification methods. 17 Thus, these protocols could not provide estimates of patient-specific first and subsequent pass hepatic extraction (x L and n L , respectively) and U N values.…”
Section: Design Strategy Of the Various Proposed Protocolsmentioning
confidence: 98%
“…[14][15][16] Subsequent investigation has shown that the cost of the original DISST could be significantly reduced by eliminating the insulin and C-peptide assays with only a moderate associated reduction in accuracy. 17,18 Using only glucose measurements, the quick dynamic insulin sensitivity test (DISTq) is able to identify SI in real time. 17,18 Although the DISTq can generate participant-specific SI values at a substantially lower cost, the standard DISST provides metrics of both SI and U N to provide a comprehensive observation of the participant's metabolic health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data was fit to the DISST model using the iterative integral method (IIM) (Docherty et al, 2012, Docherty et al, 2009. Initially, C-peptide data was deconvoluted using Equations 1-2 to define U N .…”
Section: Parameter Identificationmentioning
confidence: 99%